Carlos P. Garcia an annotated bio-bibliography, 1957-1971 - Barraquiel, Josefina A.; Hidalgo, Namnama P.; Nivera, Pat I. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1974)
This annotated bio-bibliography of Carlos P. Garcia, fourth President of the Republic of the Philippines, compiles and annotates works by and about Garcia published from the beginning of his tenure as President of the Philippines in 1957 to the time of his death in 1971. It consists of three chapters: Chapter I is the Introduction; Chapter II is the Biography of Carlos P. Garcia; and Chapter III is the Bibliography proper.
The bibliography proper is arranged in two parts: Part A consists of articles about Garcia from 1957 to 1971 in chronological order, and Part B consists of works by Garcia arranged according to types: administrative orders, appointments and designations, articles, communiques, executive orders, messages, proclamations, and speeches. Under each of these subheadings, entries are chronologically arranged. An index to these materials with instructions for use, is provided to facilitate the location of specific items.
Typescript.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Garcia, Carlos Polistico--Bio-bibliography.